2016
DOI: 10.1038/srep32842
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Yoking and Tunable Interactions in FePt-Based Hard/Soft Bilayers

Abstract: Magnetic interactions in magnetic nanostructures are critical to nanomagnetic and spintronic explorations. Here we demonstrate an extremely sensitive magnetic yoking effect and tunable interactions in FePt based hard/soft bilayers mediated by the soft layer. Below the exchange length, a thin soft layer strongly exchange couples to the perpendicular moments of the hard layer; above the exchange length, just a few nanometers thicker, the soft layer moments turn in-plane and act to yoke the dipolar fields from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
(119 reference statements)
0
21
0
Order By: Relevance
“…After deposition, the samples were processed by rapid thermal annealing (RTA) at 700 C for 30 s in N 2 atmosphere. It has been demonstrated that RTA processing of FePt/Cu bilayers does not only lead to chemical ordering but also to the development of a (001) texture on amorphous substrates, [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]68 which reveals the high potential of an RTA process for the fabrication of future FePt-based devices.…”
Section: B Fecupt/fe Ecc Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…After deposition, the samples were processed by rapid thermal annealing (RTA) at 700 C for 30 s in N 2 atmosphere. It has been demonstrated that RTA processing of FePt/Cu bilayers does not only lead to chemical ordering but also to the development of a (001) texture on amorphous substrates, [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]68 which reveals the high potential of an RTA process for the fabrication of future FePt-based devices.…”
Section: B Fecupt/fe Ecc Mediamentioning
confidence: 99%
“…Recently, the magnetic reversal behavior in hard/soft bilayer thin-films with 90 coupling angle has been discussed. 51 Furthermore, heat assisted magnetic recording composite media, consisting of a superparamagnetic writing layer and a (doped) FePt storage layer, were proposed. 52 The advantages include reduced sensitivity to T C variance in the storage layer, and the opportunity to significantly lower the T C of the FePt storage layer without increasing the T C distributions, which adversely affect the recording performance.…”
mentioning
confidence: 99%
“…Such a "left-bending boomerang" feature 7 in the corresponding M-FORC distribution is typically associated with systems that exhibit domain nucleation and abrupt propagation [33], where domain growth is dominated by a strong exchange interaction [29]. Due to the presence of the exchange and dipolar interaction, the magnetization reversal in the spin-ice system usually takes place via DW nucleation from the sample edges, and propagate through the interconnections to form the Dirac strings [8,9,18].…”
Section: Methodsmentioning
confidence: 99%
“…shows a "left-bending boomerang" feature [33], which consists of a horizontal ridge for Hr >-330 Oe and a valley-peak pair for more negative Hr. Such a "left-bending boomerang" feature 7 in the corresponding M-FORC distribution is typically associated with systems that exhibit domain nucleation and abrupt propagation [33], where domain growth is dominated by a strong exchange interaction [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation